Determinantes do investimento em projetos de cana-de-açúcar em goiás (2007-2010) - ZOPELARI, André Luiz Miranda Silva (2011)
This thesis aims to look into what are the factors that fundamentally determine the variation in investment projects in sugar cane in the state of Goyaz, in particular, between 2007 and 2010, which is when they start to concentrate investment projects in the state on the screen. To address this problem, five hypotheses have been proposed: the expansion of sugarcane in the period can be explained more by productivity gains that the availability of farmland, the second hypothesis states that the tax incentive may be influencing the attraction of investments. The third hypothesis suggests that investment is driven by the sale of flex fuel cars on the national level; the fourth proposes that investments can be supported by independent Tax Credit and Technical Change, representing the diffusion of technology and in anticipation of future demands. The latter inspires the possibility that economic growth municipalities of the sugarcane have influenced the GDP of the state of Goyaz. To verify these hypotheses, we adopted the methodology for quantitative tests, such as Linear Regression, and indirect observation of the facts and indicators. However, a reference to study the problem is not enough; therefore, it was chosen a theoretical system covering the Keynesian Investment Theories, theories of innovation and technology diffusion, led by Schumpeter and his followers. The general conclusions were that there seems no evidence that the expansion of sugarcane is supported by productivity gains; it seems, however, that tax incentives actually influence the attraction of investment; yet, the tests allow us to infer that it appears that investments are being driven by domestic sales of hybrid cars. It also seems to correspond to technological diffusion autonomous investment, as well as the evidence makes it seem that economic growth of municipalities upholding sugarcane has influenced the state's GDP. However, the survey revealed more: the historical process involving investments in sugar cane shows that this has had vivid influence on the development of Goyaz since the 18th century; one can certainly conclude that the reed has contributed much to the consolidation of agricultural vocation and state's economic growth since then.